Clinical practice guidelines for the management of pulp and periapical lesions in permanent dentition of the Peruvian Health Social Security (EsSalud) - Ulloa-Torres, Jose Antonio (2022)
Introduction: This article summarizes the evidence-based recommendations of the clinical practice guideline (CPG) for the treatment of patients with pulpal and periapical lesions in the Social Health Insurance of Peru (EsSalud). Objective: Provide evidence-based clinical recommendations for the treatment of patients with pulpal and periapical lesions in EsSalud. Methods: A guideline development group (GEG) was formed that included dental surgeons, specialists, and methodologists. The GEG formulated five clinical questions to be answered in this CPG. Systematic searches of systematic reviews and -when considered pertinent- primary studies were carried out in PubMed and CENTRAL during the years 2020-2021. The evidence was selected to answer each of the clinical questions posed. Evidence was selected to answer each of the clinical questions posed. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, the points of good clinical practice, and the treatment flowchart. Finally, the CPG was approved with Resolution No. 085-IETSI-ESSALUD-2021. Results: This CPG addressed five clinical questions about the management of pulpal and periapical lesions. Based on these questions, four strong recommendations, two conditional recommendations, 9 points of good clinical practice, and a flowchart were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions of the CPG for the treatment of pulpal and periapical lesions in EsSalud.